2023
DOI: 10.1111/1556-4029.15316
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of cellular material after exposure to water

Abstract: Disposing of items of forensic relevance in bodies of water is one countermeasure offenders can use to avoid detection. The impact of immersion in water has been explored for blood, saliva, and semen; however, few studies have assessed touch DNA. Here we report on the effect of exposure to water on the persistence of touch DNA over prolonged periods of time. To evaluate the persistence of cells from touch DNA, after water exposure, three substrates and two water types were tested: plastic, metal, and ceramic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recent reports prove that the type of material on which contact DNA has been deposited in water is very important. Metal surfaces provide an environment that is more conducive to the survival of the applied cellular material compared to plastic or ceramics [ 174 ]. Schmidt et al [ 175 ] reported that the amount of genetic material obtained from blood stains located on the shoe sole was significantly lower when shoes were used on a wet surface compared to a dry surface.…”
Section: Degradation Factorsmentioning
confidence: 99%
“…Recent reports prove that the type of material on which contact DNA has been deposited in water is very important. Metal surfaces provide an environment that is more conducive to the survival of the applied cellular material compared to plastic or ceramics [ 174 ]. Schmidt et al [ 175 ] reported that the amount of genetic material obtained from blood stains located on the shoe sole was significantly lower when shoes were used on a wet surface compared to a dry surface.…”
Section: Degradation Factorsmentioning
confidence: 99%
“…Visualization of the cells deposited via touch can be achieved using Diamond™ Nucleic Acid Dye (DD) and a fluorescence microscope. This method has been used in a variety of contexts [27][28][29][30][31][32], but the use of this technique to determine the efficiency of DNA recovery from a surface is limited. Visualization of cells before and after swabbing for evaluation of a swab's efficiency has been completed in a study by Haase et al [17] in 2019.…”
Section: Introductionmentioning
confidence: 99%